1998
DOI: 10.1103/physrevlett.80.4534
|View full text |Cite
|
Sign up to set email alerts
|

Phase Transition in theν=2Bilayer Quantum Hall State

Abstract: The width of the Hall plateau and the activation energy were measured in the bilayer quantum Hall state at filling factors n 2, 1, and 2͞3 by changing the total electron density and the density ratio in the two quantum wells. Their behaviors are remarkably different. The n 1 state is found to be stable over all measured range of the density difference. The n 2͞3 state is stable only around the balanced point. The n 2 state shows a phase transition between these two types of states as the electron density is ch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

19
115
1

Year Published

1999
1999
2004
2004

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(135 citation statements)
references
References 20 publications
19
115
1
Order By: Relevance
“…This behavior is presumably due to a capasitive charging energy stored in Skyrmions excited across the two layers in the coherent state [7]. These two experiments [3,6] indicate strongly the spontaneous development of the interlayer coherence in the ν = 1 BLQH state.An intriguing problem is whether an interlayer coherence develops also in the ν = 2 BLQH systems. Sawada et al have found [6] a phase transition at ν = 2 by changing the electron density continuously.…”
mentioning
confidence: 82%
See 3 more Smart Citations
“…This behavior is presumably due to a capasitive charging energy stored in Skyrmions excited across the two layers in the coherent state [7]. These two experiments [3,6] indicate strongly the spontaneous development of the interlayer coherence in the ν = 1 BLQH state.An intriguing problem is whether an interlayer coherence develops also in the ν = 2 BLQH systems. Sawada et al have found [6] a phase transition at ν = 2 by changing the electron density continuously.…”
mentioning
confidence: 82%
“…When the interlayer coherence exists, the BLQH state persists even if the electron density is arbitrarily unbalanced between two quantum wells. Sawada et al [6] have found precisely this behavior in certain BLQH states; furthermore they have found that the activation energy increases as the density difference becomes larger. This behavior is presumably due to a capasitive charging energy stored in Skyrmions excited across the two layers in the coherent state [7].…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…Second one is a spin singlet phase, which we call the ppin phase because it is also a fully pseudospin polarized one. They have been observed experimentally [9,10,11]. The last one is a canted antiferromagnetic phase (C-phase), which is predicted [12,13,14,15,16,17] between the spin and ppin phase in a phase diagram.…”
Section: Introductionmentioning
confidence: 99%